Qualitative and quantitative parameters of dynamic contrast-enhanced (DCE) MRI as a diagnostic determinant of soft tissue tumor malignancy: a study from Indonesia - Yulia Rosa Rosida; Hermina Sukmaningtyas; Sukma Imawati; Yan Wisnu Prajoko; Udadi Sadhana (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Soft tissue tumors encompass a large variety of benign and malignant lesions which are classified histologically based on the components. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a non-invasive technique that is used in differentiating benign from malignant lesions by observing the differences in the enhancement rates, index of lesion vascularity and perfusion. Therefore, this research aimed to evaluate the diagnostic efficacy of qualitative and quantitative parameters of DCE-MRI in the malignancy of soft tissue tumors. Methods The type of time-intensity curve (TIC), Ktrans, Kep, and Ve values were obtained from 30 soft tissue tumor (17 malignant and 13 benign) from patients who performed the DCE-MRI examination. The obtained values were then statistically analyzed to get the cutoff point, sensitivity, and specificity in determining the malignancy of soft tissue tumors. Results TIC, Ktrans, and Kep values were significantly differentiated into benign and malignant soft tissue tumors except for Ve. The TIC for benign soft tissue tumors was predominantly by type 2, while type 3, 4, and 5 were predominantly malignant. The AUC of the ROC curve demonstrated a diagnostic potential of Ktrans (0.873) and Kep (0.889). Furthermore, the cutoff point for Ktrans and Kep was 0.2905 and 0.3365 with a sensitivity of 88.2% and 94.1%, specificity of 84.6%, PPV of 88.2% and 88.9%, and NPV of 84.6%, and 91.7%. Conclusions Qualitative and quantitative parameters of DCE-MRI helped diagnose soft tissue tumor malignancy with a cutoff point for Ktrans 0.2905 and Kep 0.3365.